Four-rod Technique Stabilization after Pedicle Subtraction Osteotomy (PSO) for the Treatment of Thoracolumbar Hyperkyphosis Secondary to Pott Disease: A Two-Year Follow-Up Case Report - Barcelos, Alecio Cristino Evangelista Santos; Pinto, Sterphany Ohana Soares Azevedo; Teixeira, Thaise Ellen de Moura Agra; Nicolau, Rayana Ellen Fernandes (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2019)
Pedicle subtraction osteotomy (PSO) is a powerful tool for the management of sagittal misalignment. However, this procedure has a high rate of implant failure, particularly rod breakages. The four-rod technique diminishes this complication in the lumbar spine. The aim of the present study is to provide a case report regarding PSO and four-rod technique stabilization in the treatment of short-angle hyperkyphosis in the thoracolumbar (TL) junction. The authors describe the case of a patient with TL hyperkyphosis secondary to spinal tuberculosis treated with L1 PSO and fixation with a four-rod technique. There were no major surgical complications. The self-reported quality of life questionnaires (the Short-Form Health Survey 36 [SF-36] and the Oswestry disability index) and radiological parameters were assessed preoperatively, as well as 6, 12 and 24 months after surgery, and they showed considerable and sustained improvements in pain control and quality of life. No hardware failure was observed at the two-year follow-up.
Keywords: pedicle subtraction osteotomy; kyphosis; spinal tuberculosis; four-rod technique; postoperative complications; thoracolumbar spine